(untitled) (PANGEEA, 2025)
Time after the last glaciation (Würm glaciation) is characterized by profound changes in the climate of Europe. During this period stabilizes associations of plants and animals and produce significant changes in relief. In this paper we present the main geological, geomorphological and biological events occurred in the southwest area of Transylvania Depression and in Romania, in Holocene.